PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS DENGAN MENGGUNAKAN MODEL TALKING STIK DI KELAS IV SEKOLAH DASAR - Wati, Fitria; Alwi, Elma; Zuardi, Zuardi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This research was conducted due to the fact that teachers didn’t provide opportunities for students to read learning materials comprehensively As a result, their social science learning outcomes became low. It aimed at finding out and describing the planning, implementation, and the students’ learning outcomes in learning Social Science through the model. This class –action research applied both qualitative and quantitative approaches.The recapitulations of students result from the three aspect of cycle 1 in the first meeting show average 74.89%enoughIn the second meeting increase 85,71% {good} can conclude that talking stick can increase in the fourth class students of elementary school.Keywords :learning outcomes ips, Talking Stik